Repeal of the Trade Disputes Act - Labour Party pamphlet, 1946 (United Kingdom, 1946)
1946 1945-1960 "Repeal of the Trade Disputes Act - Labour Party pamphlet, 1946" [HFR0072], 1946 In April 1946, as promised in its manifesto for the 1945 General Election, the new Labour Government repealed the Trade Union and Trade Disputes Act 1927. The Act banned civil service trade unions from belonging to the TUC; made it more difficult for union members to pay the political levy; general strikes and other sympathetic action were forbidden, and there were restrictions on picketing.